Study of Concrete-Filled Square and Circular Tubes Subjected to Axial Compression Load - Chapagain, Prabesh; Pandey, Santosh; Chapagain, Gopinath (Journal of Lumbini Engineering College, 2023)
This study investigated the behavior of concrete filled tube (CFT) under axial compression load, focusing on specimens with different steel-to-concrete ratios and tube thicknesses. The load-deflection behavior, failure mode, and ultimate strength of the CFT specimens were analyzed for different tube sections, including circular and square hollow sections. The results showed that the CFT specimens exhibited a ductile behavior with stable load carrying capacity up to failure. The ultimate strength of the CFT specimens was found to increase with increasing steel-to-concrete ratio and tube thickness. The study provides useful insights into the behavior of CFTs under axial compression load, which can be used in the design of CFT structures. The use of high[1]strength steel in CFSTs can further enhance their strength and durability. The study also highlighted the influence of factors such as the size and shape of the steel tube and the compressive strength of the concrete on the strength of short CFST columns. Overall, this research can be valuable to engineers and researchers working in the field of structural and construction engineering.